2006
DOI: 10.1186/gb-2006-7-5-r38
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Antisense-mediated gene regulation

The study of two examples of endogenous genes with coding or non-coding natural antisense transcript partners provides evidence against the involvement of RNAi in the natural antisense-mediated regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Genic endo-siRNAs have been documented in several systems, predominantly in C. elegans , Drosophila and also in mouse [18,37-40]. However, in mammalian systems, the link between convergent transcription and RNA interference is controversial [41]. Our results confirm the existence of endo-siRNAs in human cells and the fact that 53% of these derive from SA loci provides circumstantial evidence that sense/antisense transcription may be involved.…”
Section: Discussionsupporting
confidence: 78%
“…Genic endo-siRNAs have been documented in several systems, predominantly in C. elegans , Drosophila and also in mouse [18,37-40]. However, in mammalian systems, the link between convergent transcription and RNA interference is controversial [41]. Our results confirm the existence of endo-siRNAs in human cells and the fact that 53% of these derive from SA loci provides circumstantial evidence that sense/antisense transcription may be involved.…”
Section: Discussionsupporting
confidence: 78%
“…However, siRNAs generated from bidirectional transcription of the 5Ј-UTR of L1 retrotransposons have been identified in human cells that play a role in suppressing retrotransposition (70). Others have argued that the RNA interference pathway is not importantly involved in the regulation of natural S/AS genes (71). This recent work demonstrated that sense and antisense RNAs are often present in different subcellular compartments and do not physically interact in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that about one third of protein-coding genes process NATs 21 . Interestingly, studies showed that the NAT regulatory mechanism is more likely a consequence of epigenetic modulation such as DNA methylation induced by NAT interaction with DNA methyltransferases and modification of chromatin structure by recruiting histone-modifying enzymes to the genomic locus, rather than the previously presumed direct degradation of the sense transcript through siRNA-like degradation mechanism for complementary sequences 21, 105, 114 .…”
Section: Involvement Of Lncrnas In Cancer and Therapeutic Implicationsmentioning
confidence: 99%